2013
DOI: 10.1177/1947601913507951
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAP Kinase Signal Transduction in Solid Tumors

Abstract: Mitogen-activated protein kinases (MAPKs) mediate a wide variety of cellular behaviors in response to extracellular stimuli. One of the main subgroups, the p38 MAP kinases, has been implicated in a wide range of complex biologic processes, such as cell proliferation, cell differentiation, cell death, cell migration, and invasion. Dysregulation of p38 MAPK levels in patients are associated with advanced stages and short survival in cancer patients (e.g., prostate, breast, bladder, liver, and lung cancer). p38 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
335
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(345 citation statements)
references
References 255 publications
(306 reference statements)
10
335
0
Order By: Relevance
“…However, previous studies have suggested an opposite role of p38 MAPK in mediating cell apoptosis and growth inhibition, which indicated that p38 MAPK serves a dual role as a regulator of cell behavior (28,29). In the present study, it was observed that emodin could promote the phosphorylation of p38, indicating that the p38 MAPK signaling pathway may exert a function in response to the type of stimulus and in a cell type specific manner.…”
Section: Discussionsupporting
confidence: 51%
“…However, previous studies have suggested an opposite role of p38 MAPK in mediating cell apoptosis and growth inhibition, which indicated that p38 MAPK serves a dual role as a regulator of cell behavior (28,29). In the present study, it was observed that emodin could promote the phosphorylation of p38, indicating that the p38 MAPK signaling pathway may exert a function in response to the type of stimulus and in a cell type specific manner.…”
Section: Discussionsupporting
confidence: 51%
“…Vitamin D 3 exhibits several antiinflammatory effects, including inhibition of p38 stress kinase signaling and the subsequent production of proinflammatory cytokines (14). P38, a member of the MAPK family, has been reported to play a key role in the malignant transformation and is required for the invasive capacity of human hepatocellular carcinoma and HNSCC cell lines (40,41). The ability of calcitriol to reduce the production of proinflammatory cytokines, such as IL6, by inhibiting p38 signaling has been demonstrated in cancer cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…55 The ultimate effect of p38 MAPK activation depends on the type of stimulus in a cell-type-specific manner. [56][57][58] To further explore the role of p38 activation in response to VX680 treatment, we treated cells with BIRB796. BIRB796 is a novel p38 MAPK inhibitor that inhibits all p38 MAPK isoforms in vitro and vivo.…”
Section: Discussionmentioning
confidence: 99%